Домашние хозяйства в воспроизводственном механизме частно-предпринимательской экономики (Путеводитель предпринимателя, 2020)
Article overall objective - to give quantitative and quality standard of a role of institutional sector «house economy» in reproduction mechanism of private-enterprise economy. On the basis of the analysis of a statistical and empirical material it is shown that while the considerable industrial-consumer, save-investment and socially-demographic potential of house economy is poorly involved in postcrisis development of the Russian economy.